2015
DOI: 10.1016/j.ijcard.2014.10.135
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic preconditioning reduces contrast-induced acute kidney injury in patients with ST-elevation myocardial infarction: A randomized controlled trial

Abstract: In patients with ST-elevation myocardial infarction, RIPC before percutaneous coronary intervention reduced the incidence of CI-AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 27 publications
6
89
2
1
Order By: Relevance
“…In the kidney, RIPC has been reported to attenuate post-ischemic injury. 4 Although RIPC reduces post-ischemic injury in many organs, its application requires foreknowledge of the ischemic event, which is difficult to anticipate in most circumstances, with the exception of surgery and transplantation. Recently, studies have attempted to circumvent this issue by modification of the reperfusion phase.…”
Section: Introductionmentioning
confidence: 99%
“…In the kidney, RIPC has been reported to attenuate post-ischemic injury. 4 Although RIPC reduces post-ischemic injury in many organs, its application requires foreknowledge of the ischemic event, which is difficult to anticipate in most circumstances, with the exception of surgery and transplantation. Recently, studies have attempted to circumvent this issue by modification of the reperfusion phase.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, RIPC initially proved effective in reducing the rate of CI-AKI in patients undergoing elective CA 75 or PCI in the setting of STEMI. 76 Preliminary data concerning the use of RIPC in CI-AKI are promising but merit verification in high-volume randomized studies.…”
Section: Chronic Kidney Disease and Cardiac Interventionsmentioning
confidence: 99%
“…In an elegant randomized controlled trial involving STEMI patients (n=94) in Japan, Yamanaka et al showed that RIC applied before PCI significantly reduced CI-AKI (10% versus 36%) compared with PCI alone [55]. Recent analysis of data from National Cardiovascular Data Registry (NCDR) Acute Coronary Treatment and Intervention Outcomes Network Registry®-Get With the Guidelines ™ (ACTION Registry–GWTG) from two PCI-hospitals in the United States utilizing RIC during helicopter transport showed that STEMI patients who received RIC during inter-facility helicopter transport were less likely to have CI-AKI compared to patients who did not receive RIC (8.7% versus 18.5%; unadjusted OR=0.42, 95% CI 0.18– 0.94, p=0.036) [56].…”
Section: Overview Of Clinical Evidence Of Renal Protection By Remote mentioning
confidence: 99%